2014
DOI: 10.1007/s00018-014-1622-3
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles induce nuclear damage in breast cancer cells, which is further amplified by hyperthermia

Abstract: nanospheres, damaged the nucleus at normal growth temperature, several of these defects were further exacerbated by mild hyperthermia. Taken together, the toxicity of gold nanoparticles correlated with changes in nuclear organization and function. These results emphasize that the cell nucleus is a prominent target for gold nanoparticles of different morphologies. Moreover, we demonstrated that RNA synthesis in nucleoli provides quantitative information on nuclear damage and cancer cell survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 54 publications
5
47
0
1
Order By: Relevance
“…the spatial separation of FC, DFC and GC . Such reorganization is accompanied by a redistribution of nucleolar proteins and changes in nucleolar activities . Some stressors go beyond these effects, as they induce the formation of the nucleolar aggresome, a stress‐induced nucleolar subcompartment with unique molecular make‐up .…”
Section: The Nucleolus Functions As a Ribosome Factory And Stress Sensormentioning
confidence: 99%
“…the spatial separation of FC, DFC and GC . Such reorganization is accompanied by a redistribution of nucleolar proteins and changes in nucleolar activities . Some stressors go beyond these effects, as they induce the formation of the nucleolar aggresome, a stress‐induced nucleolar subcompartment with unique molecular make‐up .…”
Section: The Nucleolus Functions As a Ribosome Factory And Stress Sensormentioning
confidence: 99%
“…13 Previous research showed that nuclear membranes, nuclear laminae, and nucleolar functions were compromised by small spherical Au NPs or gold nanoflowers in breast cancer cells. 67 Dam et al reported that nanoconstructs composed of nucleolin-specific aptamers and gold nanostars were transferred to the perinuclear region and induced major changes to the nuclear phenotype via nuclear envelope invaginations. 68 Therefore, the nucleus might be mechanically disturbed by ZnO NP aggregates located in the perinucleus or by the ROS induced by these aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary antibodies were further purified by pre-adsorption to immobilized proteins prepared from mammalian culture cells [14]. [15,16]. 24 hours prior to the experiment, trypsinize cells and culture overnight on glass cover slips coated with poly-L-lysine.…”
Section: Reagentsmentioning
confidence: 99%